2011
DOI: 10.1007/s11684-011-0127-9
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetic patients with non-alcoholic fatty liver disease exhibit significant haemorheological abnormalities

Abstract: Haemorheological abnormalities have been described in diabetes mellitus, as well as in non-alcoholic fatty liver disease (NAFLD). However, the relationship between the changes in liver fat content and haemorheology is unknown. The current study aims to show the correlation between haemorheological parameters and intrahepatic lipid content (IHLC) in patients with type 2 diabetes. The serum biochemical markers, such as fasting plasma glucose (FPG), haemoglobin A1c (HbA1c), liver enzymes, lipid profiles, and haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…WBV also observed to decrease in LC patients with more severe fibrosis. Among the three groups, patients with NAFLD had the highest blood viscosity, and this is consistent with the results of previous studies (1617192021). It is commonly known through many previous studies that increased blood viscosity is related to increased incidence and mortality of cardio-cerebrovascular disease (2223242526272829).…”
Section: Discussionsupporting
confidence: 92%
“…WBV also observed to decrease in LC patients with more severe fibrosis. Among the three groups, patients with NAFLD had the highest blood viscosity, and this is consistent with the results of previous studies (1617192021). It is commonly known through many previous studies that increased blood viscosity is related to increased incidence and mortality of cardio-cerebrovascular disease (2223242526272829).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, a fatty liver is associated with the metabolic syndrome, with insulin resistance being a prominent feature, regardless of BMI (26). Our observation that liver size was positively correlated with A1c levels within the diabetes group confirms the notion that an enlarged and fatty liver is associated with poor glucose control (48) and hemorheological abnormalities (12).…”
Section: Discussionsupporting
confidence: 81%
“…It has been largely demonstrated that hemorheological disorders are linked to insulin resistance, type 2 diabetes mellitus, and obesity (10,11). Those metabolic disorders are strictly linked to the development and progression of NASH (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…(MS), and cardiovascular disease (9)(10)(11). In particular RDW has been demonstrated to be a biomarker of cardiovascular disease, because it appears to reflect a state of chronic inflammation and oxidative stress, which are, as above mentioned, also physiopathologically involved in NAFLD development and progression (12).…”
Section: What Is Newmentioning
confidence: 99%